(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
There are several problems that a woman may encounter during her lifetime in relation to her periods. For instance, irregular periods, immense pain, and mood swings are all things a woman must grapple with. But while there are medications out there that can help beat these ailments, yoga can do better and help relieve the symptoms without any side effects.There has been a sharp increase in gynecological disorders such as polycystic ovarian syndrome, endometriosis, uterine prolapse, and infertility issues in recent times. Stress, unhealthy eating habits, lack of sleep and exercise, and genetics contribute to these endocrinal disorders. Yoga can help establish equilibrium in the body and set a balance between the body and mind. Research has shown that yoga is one of the best ways to counter the erratic hormonal changes that lead to PCOS. It can also improve reproductive functions by reducing stress and balancing the neurohormonal profile.Yoga is a holistic science which was originated in ancient India. Yoga could cure all diseases, which is presented scientifically, rationally, and persuasively to the public.It also gives both physical and mental health. This paper concentrates on the effects of Yoga on Gynecological problems.